Investigation of the electrical conductivity of the Moon (results and prospects) - I. I. Rokityansky; A. V. Tereshin (Геофизический журнал, 2010)
The Moon was intensively studied in 1959-1976, when the first geophysical models of the Moon interior was created. Data of lunar seismology, gravity, topography, and selenology yield clear understanding that lunar crust and mantle are substantially not uniform laterally. Nevertheless having quite few seismometers and magnetometers at the Moon, only spherically symmetric 1D preliminary models of seismic velocities and electrical conductivity were obtained. Electromagnetic (EM) sounding of the Moon uses the variations of interplanetary magnetic field (as input inducing field) measured by orbital magnetometer and secondary induced (output) magnetic field measured at lunar surface. From this data, transfer function (in frequency or time domain) of the Moon interior is calculated and inverse problem (lucking for conductivity versus depth distribution) is solved. We consider physical aspects of EM sounding, discuss its limitation and principal source of error - the asymmetry of daytime and nighttime near-the Moon plasma.